Sacroiliac Joint Ankylosis in Young Spondyloarthritis Patients Receiving Biologic Therapy: Observation of Serial Magnetic Resonance Imaging Scans. Issue 4 (14th February 2019) - Bray, Timothy J. P.; Lopes, Andre; Fisher, Corinne; Ciurtin, Coziana; Sen, Debajit; Hall‐Craggs, Margaret A.
Abstract : Objective: To assess the temporal relationship between initiating biologic therapy and magnetic resonance imaging (MRI) scores of inflammation and structural damage in young patients with spondyloarthritis. Methods: A local adolescent/young adult patient rheumatology database was searched for patients ages 12–24 years who had evidence of sacroiliitis on MRI and a clinical diagnosis of enthesitis‐related arthritis (ERA) with axial involvement or nonradiographic axial spondyloarthritis. Patients treated with tumor necrosis factor inhibitor (TNFi) therapy who had undergone a minimum of 1 MRI scan before and 2 MRI scans after starting TNFi therapy (over ≥2 years) were included. Images of the sacroiliac joints were scored for inflammation and structural abnormalities (including erosions, fat metaplasia, and fusion). The effects of TNFi therapy and of time since initiation of TNFi therapy on inflammation and structural abnormalities were assessed using a mixed‐effects regression analysis. Results: Twenty‐nine patients (ages 12–23 years) with ERA or nonradiographic axial spondyloarthritis who underwent TNFi therapy were included. Inflammation scores were significantly lower in patients receiving TNFi treatment ( P = 0.013), but there was no significant effect of time from TNFi initiation on inflammation ( P = 0.125). Conversely, there was no significant effect of active TNFi treatment on fusion scores ( P = 0.308), but fusion scores significantly increased with time from TNFi initiation ( P < 0.001); a similar positive relationship between time since biologic start and fat metaplasia scores was observed. Conclusion: TNFi therapy failed to prevent the eventual development of joint ankylosis in this cohort of young patients with spondyloarthritis, despite a substantial reduction in inflammation with TNFi therapy.